The Influenza Virus H5N1 Infection Can Induce ROS Production for Viral Replication and Host Cell Death in A549 Cells Modulated by Human Cu/Zn Superoxide Dismutase (SOD1) Overexpression - Lin, Xian (Viruses, 2016)
Highly pathogenic H5N1 infections are often accompanied by excessive pro-inflammatory response, high viral titer, and apoptosis; as such, the efficient control of these infections poses a great challenge. The pathogenesis of influenza virus infection is also related to oxidative stress. However, the role of endogenic genes with antioxidant effect in the control of influenza viruses, especially H5N1 viruses, should be further investigated. In this study, the H5N1 infection in lung epithelial cells decreased Cu/Zn superoxide dismutase (SOD1) expression at mRNA and protein levels. Forced SOD1 expression significantly inhibited the H5N1-induced increase in reactive oxygen species, decreased pro-inflammatory response, prevented p65 and p38 phosphorylation, and impeded viral ribonucleoprotein nuclear export and viral replication. The SOD1 overexpression also rescued H5N1-induced cellular apoptosis and alleviated H5N1-caused mitochondrial dysfunction. Therefore, this study described the role of SOD1 in the replication of H5N1 influenza virus and emphasized the relevance of this enzyme in the control of H5N1 replication in epithelial cells. Pharmacological modulation or targeting SOD1 may open a new way to fight H5N1 influenza virus.